PENEGAKAN HUKUM PELAKU TINDAK PIDANA PEREDARAN ROKOK TANPA PITA CUKAI BERDASARKAN UNDANGUNDANG NOMOR 39 TAHUN 2007 PERUBAHAN ATAS UNDANG-UNDANG NOMOR 11 TAHUN 1995 TENTANG CUKAI DI WILAYAH HUKUM DIREKTORAT JENDERAL BEA DAN CUKAI KOTA PEKANBARU - Nindy Axella; Erdianto Effendi; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Tobacco industries which originally tend to be home slowly developed intolarge industry. Numerous of tobacco industries from the middle to the low scalecaused disobedience, such as the companies did not pay tax label.To avoid disobedience caused by the companies, hence government in thiscase Directorate General and Custom, commit on surveillance and prevention ofthe outcome output violated with issuing various police.Criminal offence of cigarettes distribution without tax label which happnedin Pekanbaru handled by Pekanbaru’s tax and custom in 2012 seized 987.200illegal cigarettes packs without tax label from PT. SJA and in 2014 seized 100cartons with total 1.800 cigarettes packs, 1.084.000 sticks and all of that withouttax label, loaded onto trucks with BM 8807 SA license plate.Law enforcement of criminals distributing cigarettes without tax label basedon the constitution number 39 0f 2007 amendments to the law number 11 of 1995about the tax in jurisdiction Directorate General and Custom of Pekanbaru, hasnot been as effective as it should be due to the last 5 year, there are a lot of taketax label cigarettes in the market.Obstacles in the enforcement of criminal law distribution of cigarettes, andmost of the public do not even know the criminal act of ciggarettes distributionwithout tax label. And still lack of law enforcement of Tax and CustomPekanbaru.Effort to overcome this obstacles with the government lowered theadvolorum rates and increase and specific tax through minister finance ofregulation number 205/PMK.011/2014. And for the offenders given criminalssanction and financial sanction.Key word: Law offence-cigarettes without tax label